GENDER DIFFERENCES IN SPEAKING ANXIETY - Annisa Fauziah; Setyo Wati; Tri Agustini Solihati (Department of Master of Linguistic, Universitas Airlangga, 2022)
Speaking anxiety becomes a substantial matter in foreign language learning. Many studies have been discussed foreign language anxiety. Nevertheless, slight research has been undertaken on senior high school level. This research investigated Foreign Language Speaking Anxiety (FLSA) associated with male and female difference in senior high school level. This study aims to investigate whether male and female have the significant difference on students’ speaking anxiety level or not. Differential research method was used. From 77 grade IX students of SMA Terpadu Darussalam Tasikmalaya, 43 students were participated in this study. Probability sampling was used as the technique for selecting sample. A close-ended questionnaire adopted from Horwitz et.al (1986) was administrated to the participants to examine their Foreign Language Speaking Anxiety. The questionnaire has been passed validity test to determine whether it has positive consequences when they are used in practice. The result indicated that there is no statistically difference between male and female students. Although there was no statistically difference, the finding represents that females demonstrated a higher anxiety than males. Regarding to the result, it might be a light to help teacher choosing a great treatment for students’ anxiety during English language learning.